Heritage and Rural Tourism from Municipal Museums: Perspectives for Local Development - Lisbet Eunice Pérez Anzardo; Pedro Antonio Bruzón Sosa; Bertha M. Gómez Sedano; Irina Reyes Martínez (Lakhomi Journal Scientific Journal of Culture, 2025)
Municipal museums represent essential cultural institutions that connect heritage with the community and stimulate local development. Beyond their traditional functions of conservation and education, they hold significant potential to become strategic actors in rural tourism by engaging with community projects that integrate cultural, productive, and sustainable practices. This perspective opens the possibility for museums to serve as meeting spaces where heritage, identity, and local economy converge, fostering income diversification and the strengthening of community values. The study aims to analyze the genesis, evolution, and current situation of these institutions, in order to identify their methodological limitations and propose improvement actions that contribute to enhanced heritage management through the incorporation of rural tourism as a means of self-financing and local development. A qualitative approach was employed, based on documentary analysis, complemented by semi-structured interviews with community stakeholders and a comparative review of experiences in heritage management and rural tourism. In this way, municipal museums, through adequate articulation with rural initiatives, can significantly contribute to improving the quality of life of the population and consolidating the territory as an alternative tourism destination.